Quantitative MRI of kidneys in renal disease. - Kline, Timothy L.; Edwards, Marie E.; Garg, Ishan; Irazabal, Maria V.; Korfiatis, Panagiotis; Harris, Peter C.; King, Bernard F.; Torres, Vicente E.; Venkatesh, Sudhakar K.; Erickson, Bradley J. (Abdominal Radiology, 2018)
Purpose: To evaluate the reproducibility and utility of quantitative magnetic resonance imaging (MRI) sequences for the assessment of kidneys in young adults with normal renal function (eGFR ranged from 90 to 130 mL/min/1.73 m2) and patients with early renal disease (autosomal dominant polycystic kidney disease).Materials and methods: This prospective case-control study was performed on ten normal young adults (18-30 years old) and ten age- and sex-matched patients with early renal parenchymal disease (autosomal dominant polycystic kidney disease). All subjects underwent a comprehensive kidney MRI protocol, including qualitative imaging: T1w, T2w, FIESTA, and quantitative imaging: 2D cine phase contrast of the renal arteries, and parenchymal diffusion weighted imaging (DWI), magnetization transfer imaging (MTI), blood oxygen level dependent (BOLD) imaging, and magnetic resonance elastography (MRE). The normal controls were imaged on two separate occasions ≥24 h apart (range 24-210 h) to assess reproducibility of the measurements.Results: Quantitative MR imaging sequences were found to be reproducible. The mean ± SD absolute percent difference between quantitative parameters measured ≥24 h apart were: MTI-derived ratio = 4.5 ± 3.6%, DWI-derived apparent diffusion coefficient (ADC) = 6.5 ± 3.4%, BOLD-derived R2* = 7.4 ± 5.9%, and MRE-derived tissue stiffness = 7.6 ± 3.3%. Compared with controls, the ADPKD patient’s non-cystic renal parenchyma (NCRP) had statistically significant differences with regard to quantitative parenchymal measures: lower MTI percent ratios (16.3 ± 4.4 vs. 23.8 ± 1.2, p < 0.05), higher ADCs (2.46 ± 0.20 vs. 2.18 ± 0.10 × 10−3 mm2/s, p < 0.05), lower R2*s (14.9 ± 1.7 vs. 18.1 ± 1.6 s−1, p < 0.05), and lower tissue stiffness (3.2 ± 0.3 vs. 3.8 ± 0.5 kPa, p < 0.05).Conclusion: Excellent reproducibility of the quantitative measurements was obtained in all cases. Significantly different quantitative MR parenchymal measurement parameters between ADPKD patients and normal controls were obtained by MT, DWI, BOLD, and MRE indicating the potential for detecting and following renal disease at an earlier stage than the conventional qualitative imaging techniques.